Implementation of E-Government Through Dukcapil Via Online (Plavon) Service in Village - Nur Bianto; Ilmi Usrotin Choiriyah (Universitas Muhammadiyah Sidoarjo, 2023)
One form of e-government implementation carried out by the Office of Population and Civil Registration of Sidorjo Regency is by issuing the latest breakthrough in managing Population administration in the form of online services (PLAVON). The purpose of this study is to describe and implement e-government through online services (PLAVON) for dukcapil and to find out and describe the obstacles in implementing e-government through services via online (PLAVON) dukcapil. The type in this research is descriptive research through a qualitative approach.The implementation of e-government on legal infrastructure indicators uses guidelines through regulations from the Sidoarjo Regency Government. Second, institutional infrastructure, namely coordination with related parties at the Population and Civil Registration Office of Sidoarjo Regency. Third, human infrastructure, namely Pulungan Village government employees, they understand very well the use of online services (Plavon). Fourth, technological infrastructure, namely the existing facilities in Pulungan Village itself, is also good, there are facilities and infrastructure. While the obstacles in implementing e-government are the lack of socialization from the Pulungan Village Government, the internet network is less stable, and not all people can access the Plavon application, especially for the elderly or elderly.